Islamism, Arab Spring, and the Future of Democracy World System and World Values Perspectives - Grinin, Leonid; Korotayev, Andrey; Tausch, Arno (Perspectives on Development in the Middle East and North Africa (MENA) Region, 2019)
XVII, 364 p. 50 illus., 45 illus. in color.